Corporate debt restructuring and firm performance: A study of Indian firms - Kaur, Deepika; Srivastava, Shashi (Serbian Journal of Management, 2017)
Corporate Debt Restructuring (CDR) mechanism was initiated by the Reserve Bank of India (RBI) in the year 2001 as a remedial measure for preventing delinquency in the accounts of corporate facing financial difficulties due to internal and external factors. In this study an attempt has been made to analyze the effectiveness of the CDR system in improving the profitability of the firms. The sample consists of 91 firms that received debt restructuring package under the system form the year 2003-2015. The post-restructuring performance of the firms has been compared with their pre-restructuring performance and with their industry peers with the help of Wilcoxon sign rank test. The performance has been measured with the help of operating margin (EBDITA as a percentage of total income) and interest coverage ratio. The findings of this study reveal that sample firms were not able to improve their performance even up to five years after debt restructuring and they were performing significantly below their industry peers.
Keywords: CDR; business performances; restructuring; Corporate debt